161 Brain Activation Assessed with Functional Near-Infrared Spectroscopy (FNIRS) During Stepping and Gait in Older People and Those with PD. (20th December 2019) - Menant, Jasmine; Pelicioni, Paulo; Okubo, Yoshiro; Canning, Colleen; Sturnieks, Daina; Lord, Stephen
Abstract: Background and Aim: Past research has shown that compared with healthy peers, people with Parkinson's Disease (PD) generate poorer stepping responses and display reduced ability to adapt gait to unexpected targets and obstacles. However, the neural basis of these impairments in PD is unclear. Here, we aimed to investigate cortical activation in pre-frontal and motor areas using functional near-infrared spectroscopy (fNIRS) during stepping and gait adaptability in people with PD, compared with healthy adults. Methods: Forty-four people with PD (>40 years, Hoen & Yahr stage 1-3) and 44 healthy age and sex-matched healthy adults performed three cognitively-demanding stepping tasks and a test of gait adaptability. We recorded relative changes in oxy-haemoglobin (HbO) and deoxy-haemoglobin (HbR) concentrations in the dorsolateral prefrontal cortex, supplementary motor area, premotor cortex and primary cortex using fNIRS. Results: Data collection is ongoing with >75% participants already assessed. We will conduct between group-comparisons to compare HbO and HbR concentrations in the selected regions of interest in the stepping and the gait adaptability tests. Physical and cognitive predictors of brain activation in each task in each group will also be computed using regression models. Conclusion: Based on the results of our recent systematic review of fNIRS-recorded brain activation during walking tasks (1), we hypothesise that compared with healthy-aged matched peers, people with PD will show increased prefrontal and motor cortices activation during stepping and gait adaptability tests. This would suggest that people with PD require more attentional resources for safe walking. Reference: (1) Pelicioni et al. Prefrontal cortical activation measured by fNIRS during walking: effects of age, disease and secondary task. Peer J 2019; 7: e6833.